The artificial kidney dialysis to treat acute renal failure by LOXOSCELISM - Maya Rodríguez, Luis Enrique (1964)
1 - . Were submitted 3 cases of Acute Renal Loxosceles laeta produced and who were treated with artificial kidney. 2 - . Artificial Kidney saved the lives of 2 patients , allowing the recovery of renal function . 3 - . Loxoscelism Anuria caused by one of the cases, it was the longest among all observed by different etiologies in the Service of Metabolic and Kidney Diseases. April . Nitrogen retention and anuria were significant in all 3 cases of acute renal failure due Loxoscelism . May . The Artificial Kidney should be used when there are clinical manifestations of uremia and hyperkalemia , as occurred in our 3 cases. 6. Recovery of renal function was total for N9 1, as demonstrated by the practiced control to 2 ½ years of the bite. 7. The manifestations of aggression loxoscélica Acute Renal give gravity to the process and in most cases the renal injury is the cause of death. 8. Skin lesions caused by Loxosceles laeta , ad - integrum repaired without plastic treatment .